Comprehensive classification and categorization of Qanat features: an interdisciplinary exploration using landscape infrastructure concept and semi-systematic review - Samira Abedi; Mojtaba Ansari; Mahdi Haghighatbin; Seyed Amir Mansouri (Environmental Systems Research, 2023)
Abstract Qanats, as traditional and intelligent water infrastructures, have garnered attention across various scientific disciplines. However, a comprehensive, holistic view of Qanats remains elusive. This study aims to identify and present a thorough perspective on Qanat features. To achieve this objective, a semi-systematic review methodology was employed. The semi-systematic or narrative review approach is well-suited for subjects that span multiple disciplines and different periods. The research process commenced with an extensive search for the keyword “Qanat” within the titles and abstracts of articles across the MagIran, ScienceDirect, Taylor and Francis, and Springer databases. Subsequently, a thematic content analysis method was applied to analyze the content of these articles. Thematic content analysis involves the identification and presentation of recurring patterns in the form of distinct themes within the textual data. At this stage, Qanat features were extracted from the articles and categorized thematically. The research findings underscore the functional significance of Qanats as vital water supply systems. Furthermore, within the realm of management, Qanats are recognized as essential water infrastructures. In light of these findings, this study incorporates relevant literature from the infrastructure domain to systematically categorize Qanat features. In the research, the Landscape approach, characterized by its objective-subjective perspective, will serve as an overarching narrative framework to comprehensively classify all Qanat features. The resulting model portrays Qanats as possessing a diverse spectrum of tangible and intangible attributes, spanning environmental, cultural, social, and economic domains. This comprehensive analysis enhances our understanding of the multifaceted nature of Qanats, facilitating their preservation and sustainable management.